Rhetoric And Politics : Baltasar Gracian and the New World Order - Talens, Jenaro, 1946-; Spadaccini, Nicholas (Book collections on Project MUSE., 1997)
Wide-ranging in focus, these essays demonstrate that the work of seventeenth-century Spanish Jesuit Baltasar Gracián offers insights into the deployment of rhetoric under the "New World Order." "Rhetoric and Politics will do much to stimulate a renewed interest in Gracián and in the originality of Spanish culture." David William Foster, Arizona State University.